HYBRID CONTRACT ON ISLAMIC MORTGAGES PRODUCT USING MURABAHAH AGREEMENT (BANK SYARIAH MANDIRI PONOROGO) - Muhammad Ghozali; Abdul Hafidz Zeid; Roifatus Syauqoti (Tasharruf: Journal Economics and Business of Islam, 2020)
Islamic banking is required to innovate with hybrid contracts, as the single contract is unable to respond to contemporary financial transactions. One of the Islamic banking products adapted from conventional banking is Islamic Mortgages (KPRS) which is applied using Murabahah, Ijarah Muntahiyyah Bi at-Tamlik (IMBT) and Mutanaqisah Mutanaqisah, but Murabahah contract still dominates compared to other akad. Nevertheless, Murabahah contract still raises a lot of debate because it contains hybrid contracts that are still a debate of scholars. In addition, KPRS products with murabahah schemes and IMBT are considered controversial products formulated from the Hilah method. The Murabahah Akad pattern is also often considered the same as conventional banking credit patterns. This article uses a qualitatively descriptive approach to which data sources are obtained with interviews, observations and documentation that are then analyzed inductive. Finally, this article found that KPRS products in Bank Syariah Mandiri use the Murabahah bil Wakalah contract which is hybrid contracts. Wakalah contract is a grant of power from the bank to the customer for home price negotiation to the developer not for home purchase. This is to reduce the risk of side streaming and the risk of return of goods. The merger of Murabahah contract and Wakalah contract has obeyed the sharia rules and does not contain the haraam which is forbidden because it contains a mashalah for banks and customers.